Digital Transformation and Innovation: A Future Vision forScientific Policies in North Africa - Al Mashai, Abulgasem Al Mashai.; Eshtiwi, Khaled (Sharwes Scientific Journal, 2025)
This research focus on the connection between scientific policies and digital transformation, and their impact on sustainable innovation in North African region, highlighting the structural and institutional challenges affecting the progression of scientific research systems. The study employs a mixed-method approach, combining quantitative analysis of statistical data (including the Global Innovation Index) with qualitative interviews with field experts. The results reveal that countries with political stability and sustained investments excel in advanced digital performance, while a significant digital gap persists between urban and rural areas. The study concludes with strategic recommendations to enhance the digital infrastructure and leverage traditional knowledge to achieve comprehensive scientific and economic development.